(untitled) (Global Journal of Science Frontier Research, 2020)
This paper presents the study of availability and profit analysis of a series-parallel system consisting of four units A, B, C and D arranged in series in which subsystem D consist of three units arranged in parallel. The system works if any of A, B, C or D work. The Markovian approach was adopted to model the system behaviour with the assumption that the failure and repair rates of each subsystem follow exponential distribution. The differential equations that described the system were formulated to analyse the probability for each state. These equations were solved recursively to obtain explicit expressions for steady-state availability, busy period of repairman and profit function. The computed results are demonstrated by graphs. The results show that increase in repair rate increases the availability and associated profit. The results of the designed model are beneficial to reliability and maintenance managers.